Case report: A 9-year systematic treatment failure of a pulmonary tuberculosis patient - Jiang, Hui; Zhu, Chendi; Qin, Liyi; Wu, Xiaoguang; Yin, Jinfeng; Guo, Yijia; Ma, Huan; Jia, Junnan; Huo, Fengmin; Xue, Yi; Gao, Mengqiu; Li, Weimin (Frontiers in Public Health, 2022)
Objective To explore the reasons of failure in a case of pulmonary tuberculosis (PTB) after 9 years systematic treatment. Methods We extracted the patients' treatment history, drug susceptibility testing (DST), Computed tomography (CT) images, and sequenced the isolated strains by whole gene sequencing (WGS). Results Although most results of the phenotypical DSTs were consistent with the genotype DST, the occurrence of gene resistance to amikacin (AMK), capreomycin (CAP), moxifloxacin (MFX) was earlier than the phenotypical DST. Based on the continuously reversed results of phenotypical DSTs, CT images in different stages and WGS, it can be confirmed that the patient was infected with two different strains of Mycobacterium tuberculosis (M.TB). Moreover, severe cavities may be another factor leading to treatment failure. Conclusion Given the suggestive effect of genotype DST is earlier than the phenotypical DST, so genotype DST can play a better guiding role in patients with MDR-TB. Additionally, for patients who have not been cured for a long time, medication should be more cautious and the role of WGS in drug resistance surveillance should be fully utilized.